Mineralogy, petrology, chronology, and exposure history of the Chelyabinsk meteorite and parent body. (28th September 2015) - Righter, K.; Abell, P.; Agresti, D.; Berger, E. L.; Burton, A. S.; Delaney, J. S.; Fries, M. D.; Gibson, E. K.; Haba, M. K.; Harrington, R.; Herzog, G. F.; Keller, L. P.; et al.
Abstract Three masses of the Chelyabinsk meteorite have been studied with a wide range of analytical techniques to understand the mineralogical variation and thermal history of the Chelyabinsk parent body. The samples exhibit little to no postentry oxidation via Mössbauer and Raman spectroscopy indicating their fresh character, but despite the rapid collection and care of handling some low levels of terrestrial contamination did nonetheless result. Detailed studies show three distinct lithologies, indicative of a genomict breccia. A light‐colored lithology is LL5 material that has experienced thermal metamorphism and subsequent shock at levels near S4. The second lithology is a shock‐darkened LL5 material in which the darkening is caused by melt and metal‐troilite veins along grain boundaries. The third lithology is an impact melt breccia that formed at high temperatures (~1600 °C), and it experienced rapid cooling and degassing of S2 gas. Portions of light and dark lithologies from Chel‐101, and the impact melt breccias (Chel‐102 and Chel‐103) were prepared and analyzed for Rb‐Sr, Sm‐Nd, and Ar‐Ar dating. When combined with results from other studies and chronometers, at least eight impact events (e.g., ~4.53 Ga, ~4.45 Ga, ~3.73 Ga, ~2.81 Ga, ~1.46 Ga, ~852 Ma, ~312 Ma, and ~27 Ma) are clearly identified for Chelyabinsk, indicating a complex history of impacts and heating events. Finally, noble gases yield young cosmic ray exposure ages, near 1 Ma. These young ages, together with the absence of measurable cosmogenic derived Sm and Cr, indicate that Chelyabinsk may have been derived from a recent breakup event on an NEO of LL chondrite composition.